2015
DOI: 10.1002/rcm.7206
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric pressure anion mass spectrometry: electron affinities and activation energies of thermal electron attachment – perfluoromethylcyclohexane, C7F14

Abstract: There are multiple anions of c-C6 F11 -CF3 more stable than the neutral. Electron-capture detection and atmospheric pressure negative ion mass spectrometry are effective general methods for determining multiple electron affinities similar to the photodetachment, flowing afterglow, magnetron, negative surface ionization, swarm and beam procedures. Semi-empirical theoretical calculations support experimental results. Additional mass analysis studies of reactions of c-C6 F11 -CF3 with electrons over a wide range … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 43 publications
3
4
0
Order By: Relevance
“…The HIMPEC for the 54 superoxide spin states in Fig. are improvements over the previous literature curves, and support the theoretical predictions of the 90 superoxide states and recent communications in this journal presenting HIMPEC for multiple anion states of SF 6 and C 7 F 14 from the temperature dependence of our APIMS data and literature surface ionization, beam and flowing afterglow data . The dramatic temperature dependence of the O – distributions cannot be explained by the 54 states shown in Fig.…”
Section: Discussionsupporting
confidence: 88%
“…The HIMPEC for the 54 superoxide spin states in Fig. are improvements over the previous literature curves, and support the theoretical predictions of the 90 superoxide states and recent communications in this journal presenting HIMPEC for multiple anion states of SF 6 and C 7 F 14 from the temperature dependence of our APIMS data and literature surface ionization, beam and flowing afterglow data . The dramatic temperature dependence of the O – distributions cannot be explained by the 54 states shown in Fig.…”
Section: Discussionsupporting
confidence: 88%
“…The ionization energy of hexacene in the NIST database 6.36 (2) eV and that of naphtho[1,2‐b]triphenylene 7.40 (2) eV give AE a = EN‐IE of 8.00 − 6.36 = 1.64 eV and 8.00 − 7.40 = 0.60 eV, in agreement with the reported AE a values of 1.58 (5) eV and 0.61 (3) eV from half‐wave reduction potentials . Finally, it is suggested that, assuming that thermal decomposition does not take place, the ground state AE a of hexacene and pentacene could be measured from high‐temperature mass spectrometric thermal data as applied to SF 6 and C 7 F 14 …”
Section: Discussionsupporting
confidence: 80%
“…The ionization energy of hexacene in the NIST database 6.36 (2) eV and that of naphtho [ Table 1 [Color figure can be viewed at wileyonlinelibrary.com] thermal decomposition does not take place, the ground state AE a of hexacene and pentacene could be measured from high-temperature mass spectrometric thermal data as applied to SF 6 and C 7 F 14 . 20,23 ORCID Edward S. Chen http://orcid.org/0000-0003-3040-7816…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations